Characterization of heparan sulfate N-deacetylase/N-sulfotransferase isoform 4 using synthetic oligosaccharide substrates - Li, Yi-Jun; Yin, Feng-Xin; Zhang, Xin-Ke; Yu, Jie; Zheng, Shuang; Song, Xin-Lei; Wang, Feng-Shan; Sheng, Ju-Zheng (Biochimica et biophysica acta, 2018)
The final structure of heparan sulfate chains is strictly regulated in vivo, though the biosynthesis is not guided by a template process. N-deacetylase/N-sulfotransferase (NDST) is the first modification enzyme in the HS biosynthetic pathway. The N-sulfo groups introduced by NDST are reportedly involved in determination of the susceptibility to subsequent processes catalyzed by C5-epimerse and 3-O-sulfotransferases. Understanding the substrate specificities of the four human NDST isoforms has become central to uncovering the regulatory mechanism of HS biosynthesis. Highly-purified recombinant NDST-4 (rNDST-4) and a selective library of structurally-defined oligosaccharides were employed to determine the substrate specificity of rNDST-4. Full-length rNDST-4 lacks obvious N-deacetylase activity, and displays only N-sulfotransferase activity. Unlike NDST-1, NDST-4 did not show directional N-sulfotransferase activity while the N-deacetylase domain was inactive. Individual NDST-4 could not effectively assume the key role in the distribution of N-S domains and N-Ac domains in HS biosynthesis in vivo. •Full-length NDST-4 lacks N-deacetylase activity.•NDST-4 displays only N-sulfotransferase activity.•N-sulfotransferase activity of NDST-4 did not show directional characteristic.•NDST-4 plays limited role in heparan sulfate biosynthesis.